Secondary Atomization of Fuel Oil and Fuel Oil/Water Emulsion through Droplet-Droplet Collisions and Impingement on a Solid Wall; Energies; Vol. 16, iss. 2 - Islamova A. G. Anastasiya Gomilievna; Tkachenko P. P. Pavel Petrovich; Shlegel N. E. Nikita Evgenjevich; Kuznetsov G. V. Geny Vladimirovich (2023, 2023)
Title screen